"That's the Spiritual Side of Me": Men's Autobiographical Accounts of Recovery in Twelve Step Fellowships - Rodriguez-Morales, Lymarie (Implicit religion, 2019)
This study explores young adult men's lived experience of addiction recovery through their involvement in Twelve Step fellowships' spirituality. Although there is a large body of research on Twelve Step's recovery model, few studies have examined young adult men's psychological and identity transformation in light of its spiritual principles. Ten men participating in Twelve Step fellowships in the UK were recruited and invited to write a topical autobiography of their recovery. Data were analysed using interpretative phenomenological analysis. Participants in early recovery (six months to two years in recovery) provided accounts mostly concerned with maintaining abstinence and incorporating the Twelve Step spiritual principles and practices into their lives. Participants in long-term recovery (five to ten years) portrayed "personal growth" narratives, reflecting on their involvement with the fellowships through their life-course. Values of belonging, authenticity, care and love were identified as significant themes in their narratives and continue to infuse their identities long after initial sobriety establishment. The findings suggest that participants' spirituality evolves into a loving and caring masculine identity, which is key to their psychological development into mature adulthood. It is suggested that amidst the variety of spiritual recovery experiences (religious, atheist or secular) within the Twelve Step programmes, members share life-enhancing values that support the transcendence of their addiction.